Systematic Review of Research Instruments Measuring Competence of Nursing Clinical Preceptors - Hartini Mansyur; Nurfika Asmaningrum; Dodi Wijaya (Universitas Pahlawan Tuanku Tambusai, 2025)
Clinical preceptors are essential to nursing education because they help students learn clinical skills and develop as professionals. However, assessing preceptor competency can be challenging due to the lack of standardized and reliable tools. While various tools are available to measure multiple aspects of competency, there is no clear agreement on how these tools should be selected or used across clinical settings. The purpose of this systematic review was to identify and evaluate tools measuring competence of nursing clinical preceptor. The review focused on the instruments and their psychometric qualities, how they are used, and how effective they are in improving clinical education. A systematic literature review was conducted to identify existing instruments used to measure the level of competency of nursing clinical preceptors. Science Direct, Google Scholar, Sage Journal, Pubmed, and Springer were the databases selected for this study. Of the 13 eligible articles in this study, 12 different instruments were found. The instruments found included the Clinical Educators' Competence Questionnaire, Clinical Teaching Competence Inventory, Maastricht Clinical Teaching Questionnaire (MCTQ), Preceptors Orientation Competence Instrument (POCI), Preceptors' Competency Domain Guide Tool, Clinical Core Competency of Preceptors (CCCP), Clinical Preceptor Experience Evaluation Tool (CPEET), Competence of Clinical Nurse Educators Instrument, Nursing Clinical Teacher Effectiveness Inventory (NCTEI), Mentors' Competence Instrument (MCI), Mentorship Effectiveness Scale, IMSOC Questionnaire. Although there are several tools available to evaluate nursing clinical preceptor competency, each has its advantages and disadvantages, according to the review's findings. For a thorough evaluation, the suitable instruments must be chosen depending on particular educational circumstances. The results show that these instruments need to be further developed and standardized to increase their applicability and reliability in a variety of healthcare settings. This will ultimately assist successful preceptorships and raise the caliber of nursing education.